Complete Revascularization by Percutaneous Coronary Intervention for Patients With ST‐Segment–Elevation Myocardial Infarction and Multivessel Coronary Artery Disease: An Updated Meta‐Analysis of Randomized Trials. Issue 12 (16th June 2020) - Ahmad, Yousif; Howard, James P.; Arnold, Ahran; Prasad, Megha; Seligman, Henry; Cook, Christopher M.; Warisawa, Takayuki; Shun‐Shun, Matthew; Ali, Ziad; Parikh, Manish A.; Al‐Lamee, Rasha; Sen, Sayan; et al.
Abstract : Background: For patients with ST‐segment–elevation myocardial infarction (STEMI) and multivessel coronary artery disease, the optimal treatment of the non‐infarct‐related artery has been controversial. This up‐to‐date meta‐analysis focusing on individual clinical end points was performed to further evaluate the benefit of complete revascularization with percutaneous coronary intervention for patients with STEMI and multivessel coronary artery disease. Methods and Results: We systematically identified all randomized trials comparing complete revascularization with percutaneous coronary intervention to culprit‐only revascularization for multivessel disease in STEMI and performed a random‐effects meta‐analysis. The primary efficacy end point was cardiovascular death analyzed on an intention‐to‐treat basis. Secondary end points included all‐cause mortality, myocardial infarction, and unplanned revascularization. Ten studies (7542 patients) were included: 3664 patients were randomized to complete revascularization and 3878 to culprit‐only revascularization. Across all patients, complete revascularization was superior to culprit‐only revascularization for reduction in the risk of cardiovascular death (relative risk [RR], 0.68; 95% CI, 0.47–0.98; P =0.037; I 2 =21.8%) and reduction in the risk of myocardial infarction (RR, 0.65; 95% CI, 0.54–0.79; P <0.0001; I 2 =0.0%). Complete revascularization also significantly reduced the risk of unplanned revascularization (RR, 0.37; 95% CI, 0.28–0.51; P <0.0001; I 2 =64.7%). The difference in all‐cause mortality with percutaneous coronary intervention was not statistically significant (RR, 0.85; 95% CI, 0.69–1.04; P =0.108; I 2 =0.0%). Conclusions: For patients with STEMI and multivessel disease, complete revascularization with percutaneous coronary intervention significantly improves hard clinical outcomes including cardiovascular death and myocardial infarction. These data have implications for clinical practice guidelines regarding recommendations for complete revascularization following STEMI.